Shade effects on growth, photosynthesis and chlorophyll fluorescence parameters of three Paeonia species - Wan, Yingling (PeerJ, 2020)
Insufficient light intensity inhibits the growth of cultivated herbaceous peony and decreases its economic value. Owing to the increased demand for shade-tolerant herbaceous peony, the selection of appropriate parents for hybridization is essential. Paeonia anomala, Paeonia intermedia and Paeonia veitchii can grow under shade conditions in their natural habitats; however, their photosynthetic capacities under shade have not been studied. In this study, we simulated low light intensity (30% sunlight) and evaluated the morphological, photosynthetic and chlorophyll fluorescence parameters of these three species. Moreover, the shade tolerance of these species as well as two common cultivars (Paeonia lactiflora ‘Da Fugui’, which is suitable for solar greenhouse cultivation, and P. lactiflora ‘Qiao Ling’, which is not suitable for solar greenhouse cultivation) was evaluated. The results showed that under shade, the leaf area of P. anomala and P. intermedia increased, the single flowering period of P. intermedia and P. veitchii was prolonged, and the flower color of P. veitchii faded. With respect to P. anomala, P. intermedia and P. veitchii, shade eliminated the photosynthetic ‘lunch break’ phenomenon and decreased photoinhibition at midday. Furthermore, the maximum photochemical efficiency (Fv/Fm) and maximum primary photochemical yield (Fv/Fo) of photosystem II (PSII) in the three species improved significantly, and their changes in light dissipation were different. The shade tolerance of the tested accessions was in the order P. veitchii > P. intermedia > P. anomala > ‘Da Fugui’ > ‘Qiao Ling’, showing that the three wild species were better adapted to low light intensity than the cultivars. Thus, P. anomala, P. intermedia and P. veitchii could potentially be used in the development of shade-tolerant herbaceous peony cultivars.